Mathematical modelling - Elliott, Novak (2014)
© Springer-Verlag Berlin Heidelberg 2014. This chapter aims to make the concept of mathematical modelling—a theoretical representation of a physical system—more accessible to clinicians, thus facilitating closer collaborations with mathematicians and engineers. The basic physics behind mathematical modelling is explained, including the laws of mechanics and the fundamentals of biomechanics. The process of constructing a mathematical model and making predictions is discussed. The authors reviews the mechanics of the healthy cerebrospinal system and the situation in syringomyelia, considering the differences between syrinxes that develop as a result of obstruction to CSF channels, as compared to those associated with cord tethering.